ThinSight: a thin form-factor interactive surface technology - Izadi, Shahram; Hodges, Steve; Butler, Alex; Buxton, Bill (Communications of the ACM, 2009)
ThinSight is a thin form-factor interactive surface technology based on optical sensors embedded inside a regular liquid crystal display (LCD). These augment the display with the ability to sense a variety of objects near the surface, including fingertips and hands, to enable multitouch interaction. Optical sensing also allows other physical items to be detected, allowing interactions using various tangible objects. A major advantage of ThinSight over existing camera and projector-based systems is its compact form-factor, making it easier to deploy in a variety of settings. We describe how the ThinSight hardware is embedded behind a regular LCD, allowing sensing without degradation of display capability, and illustrate the capabilities of our system through a number of proof-of-concept hardware prototypes and applications.